A New Insight of MicroRNA-96 In Human Malignant Disorders and Drug Resistance - Zanko Hassan Jawhar; Hozan I. Ibrahim; Yousif Mohammed Younis (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
miRNA-96 is a short non-coding RNA molecule which plays an essential function in the regulation of post-transcriptional gene, and play a role in the development of a number of illnesses, such as cancer, depending on the cellular setting, it may function as a tumor suppressor or an oncogene. According to a recent research, miRNA-96 levels has been decreased in gastric cancer, breast cancer, pancreatic cancer, renal cancer and cervical cancer. However, the levels of miRNA-96 in several kinds of cancers are increased, including colorectal, lung, prostate, glioma, osteosarcoma, and hepatocellular carcinoma. The current review aims to offer a summary of miRNA-96's role in the advancement of cancer illnesses and with an emphasis on dysregulated signaling pathways. Based on in vivo, in vitro, and human research, we also go over the function of this miRNA-96 as a cancer biomarker of prognosis and emphasize how it contributes to drug resistance.